2005
DOI: 10.1111/j.0906-6705.2005.0266l.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual hormones utilize complex mechanisms to modulate sebocyte differentiation

Abstract: UV-exposition is considered as the main reason for the development of cancers of the skin. However, 90 to 100% of the Vitamin-D reqirement is formed within the skin through the action of sunlight. Considering the results of epidemiological studies, that have detected an association of Vitamin-D deficiency with various types of cancer (e.g. colon-, prostate-and breast cancer), this is a real dilema. The cancer protective effect of vitamin-D is contributed to the extra renal, local production of 1a,25(OH) 2 D 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This is in good agreement with the ageing phenotype, because it is known that the number and the functionality of capillary structures decrease with age. 1 The exact molecular mechanismswere not addressed in the present study; however, our data indicate that the secretion of miR-126 is affected rather than its basal endogenous expression. In the literature, the participation of active secretory mechanisms for miRs has been reported via (A) exosome-mediated delivery of miRNAs via NSmase as suggested by Bang et al 7 in a model of crosstalk between cardiac cells or (B) mediated by Rab proteins emphasized in a recent study in endothelial cells.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…This is in good agreement with the ageing phenotype, because it is known that the number and the functionality of capillary structures decrease with age. 1 The exact molecular mechanismswere not addressed in the present study; however, our data indicate that the secretion of miR-126 is affected rather than its basal endogenous expression. In the literature, the participation of active secretory mechanisms for miRs has been reported via (A) exosome-mediated delivery of miRNAs via NSmase as suggested by Bang et al 7 in a model of crosstalk between cardiac cells or (B) mediated by Rab proteins emphasized in a recent study in endothelial cells.…”
mentioning
confidence: 70%
“…This is in good agreement with the ageing phenotype, because it is known that the number and the functionality of capillary structures decrease with age. 1 The exact molecular mechanisms…”
Section: Discussionmentioning
confidence: 99%
“…Under the stimulation of androgens, sebum has thermoregulatory and repelling properties (40). Androgens and peroxisome proliferators-activated receptor (PPAR) ligands as well as oestrogens and the complex insulin-like growth factor-I ⁄ insulin-like growth factor-I receptors modify lipid synthesis (41,42). On the other hand, the levels of squalene, another prominent sebaceous lipid, are decreased by antihistamines in vitro, whereas human sebocytes express histamine 1 receptors in vivo and (18,19,37) Highly complex acetylcholine receptor expression pattern (70) Preservation of characteristics of stem-like cells despite their terminal cell differentiation programme (47,48)…”
Section: The Sebaceous Gland and Its Functionsmentioning
confidence: 99%
“…Zouboulis et al (266) showed that, in sebocytes, the expression of peroxisome proliferator-activated receptor (PPAR) ␥, postulated to be required for androgen-induced lipogenesis, was down-regulated by the phytoestrogen genistein, whereas E2 enhanced the metabolism of prostaglandin D2 to ⌬12-prostaglandin J2, a natural PPAR␥ ligand. Additionally, the same group found that E2 increases IGF-I synthesis and down-regulates IGF-I receptor expression (266).…”
Section: Estrogen Target Genes In the Pilosebaceous Unitmentioning
confidence: 99%